Ultrosonografía doppler color placentario-fetal en gestaciones normales de 20 a 40 semanas - Huamán Guerrero, Moisés (2001)
The objective of this study is to determine the resistance index (RI) of the umbilical artery and of the fetal mediam cerebral artery in normal subjects during the second half of pregnancy. It was carried out a longitudinal prospective study of pregnancies without complications from the 20th week through the end of pregnancy. In 125 selected pregnants the resistance index was evaluated in the umbilical artery in area free of the umbilical cord, in absence of breathing movements and with normal heart rhythm, making the reading in wave of uniform flow so that they have similar values in the different calculations. The median cerebral artery was evaluated under the same technical conditions. The evaluations of the resistance index was carried out using the software of the team LOGIO 500 MD/MR 3 of GE. The results show that the RIs of the umbilical artery and the median cerebral artery decreases progressively from the 20th through the 40th week of pregnancy. During the second half of pregnancy the RI brain – placental is higher than one. In conclusion, in normal gestations the RI of the umbilical artery is around 0,750 en the RI of the median cerebral artery is around 0,900 at 20th week of pregnancy and decrease progressively through the 40th week. This decrease is more marked between the 26 and 34 weeks in the first one. The RI of the median cerebral artery and the umbilical artery higher than I between 20 and 40 weeks.